2016
DOI: 10.1039/c6cp00643d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substituent branching and chirality on the physical properties of ionic liquids based on cationic ruthenium sandwich complexes

Abstract: An appropriate understanding of how substituents affect the physical properties of ionic liquids is important for the molecular design of ionic liquids. Toward this end, we investigated how the branching and chirality of substituents affect the physical properties of organometallic ionic liquids. We synthesized a series of ionic liquids bearing a branched or linear alkoxy group with the same number of carbons: [Ru(C5H5)(η(6)-C6H5OR)]X (rac-[1]X: R = -CH(C2H5)(C6H13), [2]X: R = -CH(C4H9)2, [3]X: R = -C9H19), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The melting points of several ILs containing branched cations have been reported. Depending on the position of the branching, cation structure, and type of paired anion, T m can either increase or decrease. ,, For example, 1-(iso-alkyl)-3-methylimidazolium-based ILs tend to show higher T m values than the corresponding linear ILs, while the opposite trend is observed for dicationic ILs . This indicates that branching involves several competing factors that influence T m .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The melting points of several ILs containing branched cations have been reported. Depending on the position of the branching, cation structure, and type of paired anion, T m can either increase or decrease. ,, For example, 1-(iso-alkyl)-3-methylimidazolium-based ILs tend to show higher T m values than the corresponding linear ILs, while the opposite trend is observed for dicationic ILs . This indicates that branching involves several competing factors that influence T m .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the FFV data discussed above, which suggest high viscosity in the branched ILs, there are two competing factors involved in the viscosity of branched ILs, i.e., bulkiness and interaction energy, according to previous works on the viscosity of branched molecules. 13,14,64,73−75,85,92−97 The viscosity increase upon alkyl chain branching has been observed in other ILs 14,64,[73][74][75]92 and some molecular liquids. 85 These behaviors are normally interpreted as being due to the bulkiness of branched chains.…”
mentioning
confidence: 96%
“…[31][32][33][34] We investigated the effect of chirality on the thermal properties of ILs, using organometallic ILs with chiral long-chain substituents, and revealed that the racemate tends to exhibit low crystallinity and a lower melting point than that of the enantiomer. 35,36 In contrast, the effect of chirality on the thermal properties of IPCs has not been elucidated, though IPCs containing a chiral quaternary ammonium cation have been reported. 37,38 Comparative thermal studies involving racemates have been conducted on neutral chiral plastic crystals such as camphor.…”
Section: Introductionmentioning
confidence: 99%
“…Nockemann et al proved that ILs containing the hexafluoroacetylacetonate anion are immiscible with water, and they exhibit strong metal-complexing ability . Mochida et al prepared metallocenium ILs, and the corresponding research was carried out. They also prepared vapor-responsive ChILs exhibiting reversible changes in color, ChILs with solvatochromic properties, and other metal-containing ILs. , Our group has also been involved in ChIL research. For instance, we developed a class of ChILs which efficiently catalyzed the solvent-free oxidation of cyclohexene by molecular oxygen, which are highly recyclable, and prepared a series of novel alkanolamine-based ILs showing a highly efficient and excellent reversible capture of CO 2 .…”
Section: Introductionmentioning
confidence: 99%